The impact of age and sex on the occurrence of pathology in the wall of the upper gastrointestinal tract - Dyrla, Przemysław; Gil, Jerzy; Niemczyk, Stanisław; Saracyn, Marek; Kosik, Krzysztof; Czarkowski, Sebastian; Lubas, Arkadiusz (Gastroenterology Review/Przegląd Gastroenterologiczny, 2017)
Introduction : The growing incidence of gastrointestinal diseases forces to improve both imaging techniques and the identification of the population with a greater risk of a disease. Identification of lesions located inside the wall of intestinal tract or in close proximity often was not possible using endoscopy or computed tomography. Aim : The study was a retrospective evaluation of the occurrence of submucosal lesions (SML) and thickened wall (TW) of the upper gastrointestinal tract (UGIT) depending on age and sex. Material and methods : Out of 20012 gastroscopies during the 4-year follow-up study, we enrolled 199 patients with pathological lesions in the wall of the UGIT. All patients underwent computed tomography and endoscopic ultrasound (EUS). Results : We analysed a total of 122 (78 males, 44 females, age: 64.0 ±12.9 years) out of 187 patients. 23.91% of SML in the oesophagus, 56.52% in the stomach, and 19.57% in the duodenum. A higher number of SMLs was found in men than in women (57.14% vs. 40.45%, p = 0.023), and the difference was greater over 50 years of age (85.71% vs. 40.00%, p = 0.031). We found less malignant SMLs compared to benign (35.87% vs. 64.13%, p = 0.026), especially in women (22.86% vs. 47.46%, p = 0.006). 26.67% of TW were in the oesophagus, 66.67% in the stomach, and 6.67% in the duodenum. There was a tendency towards increased incidence of TW over 50 years of age (8.58% vs. 18.30%, p = 0.074), which concerned men in particular (24.10% vs. 11.43%, p = 0.043). Until 65 years of age, these differences were significant for the oesophagus (27.27% vs. 0.00%, p = 0.044) and the stomach (25.93% vs. 4.00%, p = 0.029). As many as 70% of TW pathologies were malignant. Conclusions : Submucosal lesions and TW of the upper gastrointestinal tract account for 0.61% of performed gastroscopies. They occur in men and usually over 50 years of age.